TEACHERS’ OBSTACLES IN ASSESSING STUDENTS’ ATTITUDES DURING THE ONLINE LEARNING PROCESS BASED ON THE CURRICULUM OF 2013 - Silvia Auliya; Rizqi Wahyu Afanti; Rodeo Danu A; Rian Damariswara (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the teachers’ obstacles in giving attitude assessments to students from home. In addition, this paper also discusses the impact that is accused regarding the obstacle in giving attitude assessment to students and knows the solution that is used by the teacher to resolve the obstacle in giving attitude assessment. The research method used is a qualitative descriptive approach. The data collection used is an interview method. The research subject is the teachers at State Elementary School of Pelas 01 who are applying K-13 in classes 1 to 6. The research finding is that the teachers had obstacles during the learning process based on K-13. The obstacles faced by the teachers at State Elementary School ofPelas 01 who use K-13 are that the students had been late in collecting the tasks, students had not allowed Zoom Meetings, and students had not responded to their teachers. The impact of obstacles implies that teachers cannot assess the attitude through discipline, honesty, responsibility, and politeness to students. Thus, the teacher takes action to overcome these issues.